Comprehensive Studies on Detection of Palm Oil Adulteration in Clarified Milk Fat (Ghee) - Akshay Ramani; Tanmay Hazra; Ayon Tarafdar; Ranjna Sirohi; Anamika Das; Swarnima Dey; Yogesh Kumar (International Journal of Food Science)
Heat-clarified milk fat (ghee) is one of the costlier fat-rich dairy products, and palm oil adulteration is a common practice. Limited studies compared traditional physicochemical techniques with advanced chromatographic techniques and chromogenic tests (rapid tests) to ascertain palm oil’s presence in ghee. It is a very hard task to ascertain the presence of palm oil in clarified milk fat (ghee) and select the right analytical technique for routine quality control analysis. The present study was designed to validate and compare the physicochemical methods, triglyceride content, phytosterol levels, and rapid chromogenic tests including 2,2-diphenyl-1-picrylhydrazyl (DPPH) or ferric-based assay methods to check the presence of palm oil in clarified milk fat. Physicochemical methods like Reichert–Meissl (RM) value, iodine value (IV), and Butyro refractometer (BR) reading can be used to detect palm oil adulteration below 10%. However, the Kirschner value analysis was able to confirm the presence of palm oil admixture at 5% in clarified milk fat. In chromatographic analytical approaches, triglyceride analysis (S-value) was carried out using gas chromatography with flame ionization detection (GC-FID), and plant sterol detection was done by HPLC, which proved to be the robust method for ascertaining the presence of palm oil in milk fat (ghee) at 5%. Chromogenic tests (DPPH and ferric-based assays) provided quick and qualitative assays to detect the presence of palm oil in ghee at a 5% level.